Chicken Little - Dindal, Mark; Fullmer, Randy; Bencich, Steve (Walt Disney Pictures ; distributed in the Philippines by Viva Video, 2006)
After ruining his reputation with the town, a courageous chicken must come to the rescue of his fellow citizens when aliens start an invasion.